Critical approaches to genocide
1 online resource.
Keywords: "The study of genocide has been appropriate in emphasizing the centrality of the Holocaust yet other preceding episodes of mass violence are of great significance. Taking a transnational and transhistorical approach, this volume redresses and replaces the silencing of the Armenian Genocide. The interdisciplinary approach makes Critical Approaches to Genocide a useful resource for all students and scholars interested in the Armenian Genocide and memory studies"--